SEJARAH TERBENTUKNYA MARGA KERUBUN DI DESA DIAN KABUPATEN MALUKU TENGGARA - Tirani Pranti Kerubun; Debi Setiawati (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
The background of this research is the author's curiosity about the history of the formation of the Kerubun clan in Dian village, Hoat Sorbay sub-district, during the Nen Kabloat period in the land of Kabloat-Kolser village. The purpose of this writing is to find out the history of the formation of the Keluben clan in Dian Village. The research method uses a qualitative approach with descriptive analysis methods with data sources taken from interview data, observation, and documentation, while for data analysis, interactive Miles and Huberman models are used. The results of this study show that the formation of the cherub clan in Dian village started with Kabloat nen, who lived in a village, namely Kolser land, then spread to several places, one of which was Dian village, and began to develop from 1980 until now. The history of the formation of the Kerubun clan began with Kabloat nen, who lived in a village, namely Kolser Land, and then spread to several places, one of which was the village of Dian. The Kerubun clan began to develop since the 1980s in terms of education and customs, and although there are several families from the Kerubun clan who have forgotten to respond to developments that have occurred, there are still other families who must remind them to stay together to encourage generations in educational and other developments. As a response to the aspirations of the Kerubun clan in Dian village, Hoat Sorbay sub-district, Southeast Maluku district. The formation was driven by the increasing number of descendants of the Kerubun, who were able to form an identity as an educated and obedient clan with its unique and distinctive customs in Southeast Maluku Regency.